2023
DOI: 10.3390/ijms241310745
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening of a Hungarian Cohort with Focal Dystonia Identified Several Novel Putative Pathogenic Gene Variants

Abstract: Dystonia is a rare movement disorder which is characterized by sustained or intermittent muscle contractions causing abnormal and often repetitive movements, postures, or both. The two most common forms of adult-onset focal dystonia are cervical dystonia (CD) and benign essential blepharospasm (BSP). A total of 121 patients (CD, 74; BSP, 47) were included in the study. The average age of the patients was 64 years. For the next-generation sequencing (NGS) approach, 30 genes were selected on the basis of a thoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, in the Hungarian cohort study, it was found in a higher prevalence than previously reported. All three mutations identified there (c.677G>T (p.Cys226Phe), c.1315G>A (p.Val439Met) and c.1288G>A (p.Ala430Thr)) are thought to be pathogenic, and the clinical profile fits the characteristics already linked with GNAL variants [46]. (e) ANO3 (anoctamin-engaged in calcium homeostasis) ANO3-linked dystonia has an autosomal-dominant inheritance pattern, yet only heterozygous variations have been identified.…”
Section: The Genetic Background Of Dystoniamentioning
confidence: 72%
“…However, in the Hungarian cohort study, it was found in a higher prevalence than previously reported. All three mutations identified there (c.677G>T (p.Cys226Phe), c.1315G>A (p.Val439Met) and c.1288G>A (p.Ala430Thr)) are thought to be pathogenic, and the clinical profile fits the characteristics already linked with GNAL variants [46]. (e) ANO3 (anoctamin-engaged in calcium homeostasis) ANO3-linked dystonia has an autosomal-dominant inheritance pattern, yet only heterozygous variations have been identified.…”
Section: The Genetic Background Of Dystoniamentioning
confidence: 72%
“…The GNAL c.677G>T (p.Cys226Phe) variant was discovered in a male patient who has had leftsided neck pain, right-directed laterocollis, torticollis, and mild retrocollis since the age of 27 [42].…”
Section: C) Striatal Dopamine Signaling -Gnal (Guanine Nucleotide-bin...mentioning
confidence: 99%
“…The symptoms of a female patient with another GNAL c.1315G>A (p.Val439Met) variation began when she was 30 years old. The patient complained that her head began to move slightly to the left and that it became more and more challenging for her to keep it in a neutral position [42].…”
Section: C) Striatal Dopamine Signaling -Gnal (Guanine Nucleotide-bin...mentioning
confidence: 99%
See 2 more Smart Citations